Development of Mellorine type frozen desserts: 1. Effect of stabilizers and emulsifiers - ADHTKARI, KAUSHIK; ARORA, K L (The Indian Journal of Animal Sciences, 2013)
Mellorine type frozen desserts were manufactured using groundnut-oil and vanaspali ghee by standard manufacturing procedure with some modifications and compared with control ice-cream. The values of surface tension, relative viscosity melting rate and pH and sensory qualities of all types of desserts were comparable to those of control ice-cream, whereas free fat content was higher and whipping ability was lower than the control.